Highly Hydrophobic and Chemically Rectifiable Surface‐Anchored Metal‐Organic Framework Thin‐Film Devices. Issue 13 (23rd March 2016) - Rana, Shammi; Rajendra, Ranguwar; Dhara, Barun; Jha, Plawan Kumar; Ballav, Nirmalya
Abstract : Functionalizing various surfaces with metal‐organic frameworks (SURMOFs) are promising platforms for a variety of technological applications. Herein, liquid‐phase epitaxy has been employed to grow oriented and uniform SURMOF thin‐films of Cu ion and tetracyanoquinodimethane (TCNQ) ligand on self‐assembled monolayer templates. The SURMOF thin‐films of Cu‐TCNQ on fluorine doped tin oxide, Au, and polyethyleneterephthalate substrates are realized to be highly hydrophobic exhibiting contact angle of water ≈140°. SURMOF thin‐film devices of Cu‐TCNQ have been fabricated by employing electron‐beam lithography technique. Room‐temperature current–voltage ( I – V ) characteristics consistently showed non‐Ohmic semiconductivity in the range of ≈10 −5 S cm −1 . A remarkable rectification in the electrical conductance of SURMOF thin‐film device with rectification factor of ≈100 was achieved upon exposing iodine (I2 ) vapor at ambient conditions whereas bulk‐Cu‐TCNQ remains nonrectified. Even, highly hydrophobic surface nature is retained in course of gaining electrical rectification. The unusual rectifying thin‐film phenomenon induced by I2 is attributed to structural and electronic reorganization in the SURMOF and the rectification follows standard Shockley diode equation. The here presented results demonstrate a new avenue of research on MOFs where electronic and magnetic properties in particular can be efficiently explored and controlled in SURMOF thin‐film device configurations (also mechanically flexible) for various technological applications. Abstract : Highly hydrophobic and semiconducting metal‐organic framework thin‐film devices of Cu‐tetracyanoquinodimethane material are fabricated on Au and fluorine doped tin oxide substrates by employing electron‐beam lithography technique. Room‐temperature measurements consistently show non‐Ohmic I – V characteristics. Without affecting the hydrophobicity, a remarkable rectification in the electrical conductance is achieved upon exposing I2 vapor at ambient conditions.